MicroRNA-451 regulates chemoresistance in renal cell carcinoma by targeting ATF-2 gene. Issue 12 (June 2017) - Sun, Xiang; Lou, Longhua; Zhong, Kezhao; Wan, Lijuan
Renal cell carcinoma (RCC) is a malignant tumor, which severely threatens human's life, moreover, the multi-drug resistance (MDR) under RCC undoubtedly strengthen the difficulties in the treatment. MiR-451 has been considered to play an important role in regulation of MDR in several cancers, but the role of it in MDR of RCC has not been explored. This study aims to explore the mechanism of miR-451 as a target to regulate chemotherapy resistance, which is crucial for further exploring novel therapy for RCC. Two human cell lines (ACHN and GRC-1) were performed in this study and adriamycin (ADM) was used to construct MDR cell lines. qRT-PCR was used to determine the mRNA expression of miR-451 and ATF-2. Weston blot was used to determine protein expression. MTT assay and flow cytometry were used for assessing cell viability and apoptosis, individually. Luciferase reporter assay was used to detect the targeting of miR-451 and ATF-2. Results presented that the expression of miR-451 was higher in low MDR cell line (ACHN) comparing with the high MDR cell line (GRC-1), while the expression of ATF-2 revealed an opposite results. MiR-451 targeted ATF-2 and regulated its expression. Overexpression of miR-451 strengthened drug resistance, decreased cell viability, and increased cell apoptosis of GRC-1 pretreated by ADM, while overexpressed ATF-2 reversed the effect induced by miR-451 overexpression. Then miR-451 knockdown improved drug susceptibility, decreased cell apoptosis, and increased cell viability of ACHN induced by ADM, however, ATF-2 suppression reversed the low rate of cell apoptosis and high rate of cell viability induced by miR-451 knockdown. Our results revealed that miR-451 regulates the drug resistance of RCC by targeting ATF-2 gene, which might be critical for overcoming MDR in RCC patients. Impact statement: This is the first study to emphasize the expression of miR-451 on regulating multi-drug resistance (MDR) in renal cell carcinoma (RCC). Our study found that miR-451 regulates the drug resistance of RCC by targeting ATF-2, which might be critical for overcoming MDR in RCC patients. This study not only provides solid theory foundation for the clinical therapy, but also offers unique insights for the further RCC research. Furthermore, the study helps us to understand the mechanism of MDR, which was crucial for identifying the chemoresistance on several related tumors.